Malawi : Poverty Reduction Strategy-Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2005)
This paper examines the Annual Progress Report on Malawi's Poverty Reduction Strategy. Malawi could not reach its macroeconomic targets owing mainly to expansionary fiscal policies, which resulted in higher-than-envisaged domestic debt, interest rates, and inflation. The authorities aim to reduce the government's domestic debt to free fiscal resources for development expenditures and ease credit costs for private sector-led growth. The University of Malawi undertook several activities meant to increase access and equity and to reduce reliance on government subventions.